Effects of Hibiscus sabdariffa supplementation on metabolism and bladder in obese rats - Pajolli, Pedro [UNESP]; Kawano, Paulo Roberto [UNESP]; Yamamoto, Hamilto [UNESP]; Guerra, Rodrigo [UNESP]; Moraes, Bruno Matos [UNESP]; Reis, Leonardo Oliveira; Ordones, Flávio Vasconcelos; Fugita, Oscar Eduardo Hidetoshi [UNESP]; Melchert, Alessandra [UNESP]; Amaro, João Luiz [UNESP] (FapUNIFESP (SciELO), 2024)
Purpose: Hibiscus sabdariffa (HS) extract has several health benefits and anti-obesogenic effects. The aim of the present study was to assess whether the medicinal properties attributable to HS would prevent or mitigate bladder changes induced by obesity in an experimental model. Methods: Forty-eight male Wistar rats were submitted to one of four different dietary interventions (12 animals each): G1, standard diet and water (controls); G2, standard diet and HS tea; G3, a palatable high-fat diet and water; and G4, high-fat diet diet and HS tea. The animals were monitored for body weight, feed, and water and tea intake, according to the allocated group. After 16 weeks, the animals were euthanized, and the levels of creatinine, inflammatory cytokines, testosterone, cholesterol, triglycerides, and electrolytes were evaluated. In addition, histopathological analysis of the animals’ bladder was performed. Results: Groups receiving HS (G2 and G4) showed decreased levels of the pro-inflammatory cytokine interleukin-1α. HS tea was able to reduce low-density lipoprotein and triglyceride levels in the G2 group compared to other groups. Only in the G3 there was a significant increase in the body weight when it was compared the 12th and 16th weeks. Leptin was shown to be elevated in the groups that received a high-fat diet. There was a significant decrease in the muscle fibers thickness and in the total collagen count in G4 bladder when compared with G1 and G3. Conclusion: HS has an anti-inflammatory role, can reverse hyperlipidemia in rats, and reduced deleterious effects of obesity on these animals’ bladder.
Keywords: Bladder; Hibiscus; Interleukins; Metabolism; Obesity